Osteophyte growth in early thumb carpometacarpal osteoarthritis. Issue 9 (September 2019) - Crisco, J.J.; Morton, A.M.; Moore, D.C.; Kahan, L.G.; Ladd, A.L.; Weiss, A.-P.C.
Summary: Objective: Osteophyte formation is a critical part of the degeneration of a joint with osteoarthritis (OA). While often qualitatively described, few studies have succeeded in quantifying osteophyte growth over time. Using computed tomography (CT) image data from a longitudinal, observational study of thumb carpometacarpal (CMC) OA, our aim was to quantify osteophyte growth volume and location over a three-year period in men and women. Method: Ninety patients with early thumb OA were recruited and assessed at baseline, 1.5 years, and 3 years with CT imaging. Osteophyte volume and location on the trapezium and first metacarpal were determined using a library of 46 healthy subjects as a nonarthritic reference database. Results: There was a significant increase in osteophyte volume for women and men over the three-year follow-up in the trapezium (86.8 mm 3 –120.5 mm 3 and 165.1 mm 3 –235.3 mm 3, means respectively) and in the proximal metacarpal (63 mm 3 –80.4 mm 3, and 115.8 mm 3 –161.7 mm 3, respectively). The location of osteophyte initiation and growth was consistent across subjects and was located in non-opposing regions on the trapezium and first metacarpal. Osteophyte growth occurred about the radial and ulnar margins of the trapezial facet, while on the proximal metacarpal, growth occurred principally about the volar and dorsal margins of the facet. Conclusion: Osteophyte growth occurred in early thumb osteoarthritis over three years. Growth was localized in specific, non-opposing regions on the trapezium and metacarpal, raising intriguing questions about the triggers for their formation, whether the mechanisms are mechanical, biological or a combination of both.